Counter-stereotypic beliefs in math do not protect school girls from stereotype threat - Huguet, Pascal; Régner, Isabelle (Journal of Experimental Social Psychology, 2009)
The threat of being negatively stereotyped in math impairs performance of highly qualified females on difficult math tests, a phenomenon known as “stereotype threat”—ST. Perhaps more alarmingly, recent studies based on unselective samples of elementary-, middle-, and high-school students show that ST also operates in girls from the general population. Here we offer first evidence that ST does operate (with large effect sizes) even in middle-school girls who deny the negative gender stereotype. Children’s beliefs about the two genders math ability, therefore, do not necessarily moderate their susceptibility to ST, an important issue that remained unclear so far. This new finding is also of great practical significance: School girls’ counter-stereotypic beliefs cannot be taken as sufficient evidence for deciding whether the struggle against ST is or is not needed. Appropriate interventions should be the default option when aiming for true gender equality in math and science achievements.
Keywords: Counter-stereotypic beliefs; Gender; Stereotype threat; Stereotypic knowledge